2006
DOI: 10.1016/j.top.2005.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Conjugacy problem in groups of oriented geometrizable 3-manifolds

Abstract: The aim of this paper is to show that the fundamental group of an oriented 3manifold which satisfies Thurston's geometrization conjecture, has a solvable conjugacy problem. In other terms, for any such 3-manifold M , there exists an algorithm which can decide for any couple of elements u, v of π 1 (M ) whether u and v are in the same conjugacy class of π 1 (M ) or not. More topologically, the algorithm decides for any two loops in M , whether they are freely homotopic or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…Préaux [21] has shown that the conjugacy problem is solvable in the fundamental group of an orientable, geometrizable 3-manifold.…”
Section: Introductionmentioning
confidence: 99%
“…Préaux [21] has shown that the conjugacy problem is solvable in the fundamental group of an orientable, geometrizable 3-manifold.…”
Section: Introductionmentioning
confidence: 99%
“…Préaux, extending Sela's work on knot groups [102], proved that the conjugacy problem is solvable, first for the fundamental groups of orientable 3-manifolds [90], and then also for the fundamental groups of non-orientable 3-manifolds [91]. (Note that, in contrast to many other group properties, solvability of the conjugacy problem does not automatically pass to finite extensions.)…”
Section: The Conjugacy Problemmentioning
confidence: 99%
“…As we mentioned in the introduction, Préaux, extending Sela's work on knot groups [Sel93], proved that the Conjugacy Problem is solvable for the fundamental groups of orientable [Pr06] and non-orientable [Pr12] 3-manifolds. (Note that, in contrast to many other group properties, solvability of the Conjugacy Problem does not automatically pass to finite extensions [CM77].…”
Section: The Word Problem and The Conjugacy Problem For 3-manifold Grmentioning
confidence: 99%